2005
DOI: 10.1056/nejmoa050935
|View full text |Cite
|
Sign up to set email alerts
|

Drotrecogin Alfa (Activated) for Adults with Severe Sepsis and a Low Risk of Death

Abstract: The absence of a beneficial treatment effect, coupled with an increased incidence of serious bleeding complications, indicates that DrotAA should not be used in patients with severe sepsis who are at low risk for death, such as those with single-organ failure or an APACHE II score less than 25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
397
0
23

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 814 publications
(432 citation statements)
references
References 22 publications
12
397
0
23
Order By: Relevance
“…Over the past few decades, although some anticoagulant agents, such as antithrombin (AT), tissue factor pathway inhibitor, and activated protein C, have been investigated for use in patients by international large randomized controlled trials (RCTs), no remarkable effect on the mortality rate has been reported 4, 5, 6, 7. However, the post‐hoc subgroup analyses of those RCTs indicated that the anticoagulant therapies resulted in improved mortality rates in patients with sepsis‐induced DIC 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, although some anticoagulant agents, such as antithrombin (AT), tissue factor pathway inhibitor, and activated protein C, have been investigated for use in patients by international large randomized controlled trials (RCTs), no remarkable effect on the mortality rate has been reported 4, 5, 6, 7. However, the post‐hoc subgroup analyses of those RCTs indicated that the anticoagulant therapies resulted in improved mortality rates in patients with sepsis‐induced DIC 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Although this effect was of borderline significance in PROWESS (3.5% vs. 2% in the placebo group, P ϭ .06), 29 it was confirmed in subsequent trials (3.9% vs. 2.2%, P ϭ .01) 30 and may be larger still in open-label use, at 6.5%. 17,31 Intracerebral hemorrhage (ICH), a particularly devastating complication, occurred in 0.2% of the PROWESS patients and 0.5% of patients in 2 subsequent studies 30,32 ; in both major trials, there was a single extra event in the APC arm. 29,30 Like serious bleeding in general, ICH was more common in open-label use, occurring in 1.5% of patients.…”
Section: Activated Protein Cmentioning
confidence: 89%
“…32,35 The ADDRESS trial also failed to demonstrate a benefit in a subgroup of patients with APACHE II scores above 24, although it was underpowered to do so, and according to enrollment criteria, none of those patients had multiorgan failure. 30 However, in the subgroup of PROWESS patients with APACHE II scores greater than 24, the absolute reduction in mortality was a full 13%, 17 with a corresponding NNT of 7.7, and although the PROWESS findings have not been duplicated in a second randomized trial, a single-arm, open-label study of APC (ENHANCE) showed a nearly identical mortality rate. 31 Pending confirmatory trials, APC remains a recommended therapy for selected patients sick enough to benefit and without excessive bleeding risk.…”
Section: Activated Protein Cmentioning
confidence: 99%
See 2 more Smart Citations